Developing Instrument of Digital Age Literacy Inventory: Validity and Reliability Analysis Using Rasch Model - Afandi Afandi; Eko Sri Wahyuni; Anik Roslina Rosyadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
The development of a valid and reliable assessment instrument of digital-age literacy is truly required to determine the level of students' digital-age literacy competence. One major issue is the lack of standardized instruments that comprehensively measure all dimensions of digital-age literacy. This study aims to develop and analyze digital-age literacy inventory instruments (DALI) since there is no standardized instrument regarding digital-age literacy has been created. The development of the DALI is carried through three phases: research scale components identification, writing and developing the questionnaire items, and the analysis of its validity and reliability. A total of 40 statement items were developed based on the digital age literacy component. The sample of this study was 75 eleventh-graders of science State Senior High Schools in Pontianak. The data were analyzed using the Rasch Model with the help of the WINSTEP 3.73 application. The analysis results show that the total value of the Aikens V index is 0.96. DALI has obtained the value of person reliability of 0.71 (good enough), item reliability of 0.98 (excellent), and the value of Cronbach's alpha of 0.75 (good). On the whole, the statement items are declared valid based on the value of outfit MNSQ person and the item of 0,99 and the value of Outfit Z Standardized (ZSTD) in which the person analysis -0.2 and the item of -0,3. Of 40 items being analyzed, 6 items do not fit the Rasch Model, the final number of valid and usable instrument items is 34 items. The development of DALI shows that the quality of the instrument is good and can be used to measure the digital age literacy of senior high school students within the 8 components of the latter.